DESCRIPTION OF NURSES ROLE IN PROVIDING MENTAL SUPPORT TO THE PREOPERATIVE PATIENTS - Srinalesti Mahanani; Amelia Kristanti; Aries Wahyuningsih (Genius Journal, 2020)
Introduction: Surgery is performed for various reasons, for example for diagnostic, curative, reparative, recontructive, palliative. Elective and emergency surgery is a tense complex event (Digiulio, 2007). The anxiety they experience is usually associated with all kinds of foreign procedures that the patient must undergo and also the threat to life safety due to all kinds of surgical procedures and anesthesia (Majid, 2011). Objectives: The research objective was to study the description of nurses role in providing mental support to the preoperative patients at outpatient installation of Baptis Hospital Kediri, the research design was descriptive. Method: Population in this research that was all patients that would be performed operation at outpatient installation of Baptis Hospital Kediri, number of samples researched were 62 respondents. The variable of this research was nurses role in providing mental support to the preoperative patients. The instrument used by the researcher was the questionnaire, and the analysis used the descriptive frequency. Result: The results of the nurses role in providing mental support to the preoperative patients at outpatient installation of Baptis Hospital Kediri were 62 respondents obtained enough result that were 53 respondents (85.5%), got good result as many as 2 respondents (3.2%), got less than 7 respondents (11.3%). Conclusion: Conclusion of research showed that nurses role in providing mental support to the preoperative patients at outpatient installation of Baptis Hospital Kediri was enough.